Neutrophil extracellular traps as immunofibrotic mediators in RA-ILD; pilot evaluation of the nintedanib therapy - Venetsanopoulou, Aliki I.; Ntinopoulou, Maria; Papagianni, Eleni; Koletsos, Nikolaos; Voulgari, Paraskevi V.; Chrysanthopoulou, Akrivi (Frontiers in Immunology, 2024)
Objective: Rheumatoid arthritis-associated interstitial lung disease (RA-ILD) is a significant pulmonary complication of RA. This study tried to elucidate the mechanisms enhancing inflammation and causing lung injury in RA-ILD, focusing on the role of neutrophil extracellular traps (NETs). The study also investigated the potential benefits of nintedanib in advanced disease.Methods: Nine RA-ILD patients and nine healthy controls were included in the study.Inflammatory markers in patients' circulation were evaluated with immunoassays. The formation of NETs was examined using a citrullinated histone H3 (CitH3) ELISA and cell immunofluorescence. Inflammatory proteins expressed in neutrophils/NETs were studied with real-time qPCR and NET ELISA. To assess the effect of nintedanib, an intracellular tyrosine kinase inhibitor with antifibrotic properties, in RA-ILD a paired study was conducted in five patients before treatment administration and 16 weeks later.The soluble terminal complement complex sC5b-9 and the levels of CitH3 were significantly elevated in patients with RA-ILD, compared to healthy controls. In addition, neutrophils isolated from RA-ILD patients released NETs enriched with tissue factor and interleukin-17A. Inflammatory NETs had a dynamic role, increasing the fibrotic potential of human pulmonary fibroblasts (HPFs). On the other hand, nintedanib treatment decreased NETs and sC5b-9 levels in RA-ILD patients.The findings propose an interplay between circulating NETs and HPFs, establishing the immunofibrotic aspects of RA-ILD. They also support the effectiveness of nintedanib in reducing key pathological processes of the disease. Further research is needed to fully understand these mechanisms and optimize treatment strategies for RA-ILD.